1985
DOI: 10.1007/bf00923267
|View full text |Cite
|
Sign up to set email alerts
|

Community integration of the mentally III in residential facilities

Abstract: Much of the empirical research on the social adjustment of the mentally ill has focused on client variables. More recently, recognition of environmental factors as influences on behavior has led to attempts to determine environmental factors that may play a role in former mental patients' community integration. The secondary data analysis of 87 former state hospital patients in residential facilities suggests that while client characteristics are important in explaining community integration, facility, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 17 publications
5
52
1
4
Order By: Relevance
“…Indeed, various studies have shown a negative correlation between the size of the facility and social adjustment (Hull & Thompson, 1981;Kruzich, 1985;Linn et al, 1980;Nagy et al, 1988). In our study larger RFs showed, as we hypothesized, a significantly higher rate of drop-outs and escapes, and tended to have a lower rate of mutually agreed discharges.…”
Section: The Physical Environment Of Rfssupporting
confidence: 45%
See 1 more Smart Citation
“…Indeed, various studies have shown a negative correlation between the size of the facility and social adjustment (Hull & Thompson, 1981;Kruzich, 1985;Linn et al, 1980;Nagy et al, 1988). In our study larger RFs showed, as we hypothesized, a significantly higher rate of drop-outs and escapes, and tended to have a lower rate of mutually agreed discharges.…”
Section: The Physical Environment Of Rfssupporting
confidence: 45%
“…This is surprising, because there is evidence that the characteristics of both the environment and the staff can strongly affect residentsÕ quality of life and outcome (Baker & Douglas, 1990;Baker & Intagliata, 1982;Lehman, 1983). For instance, several studies have shown that the size of RFs can be negatively correlated with a variety of measures of social adjustment (Hull & Thompson, 1981;Kruzich, 1985;Linn, Klett, & Caffey, 1980;Nagy, Fisher, & Tessler, 1988). Moreover, the seminal work by Rudolph H. Moos (Moos, 1996(Moos, , 2002Moos & Lemke, 1980) and other studies have demonstrated that the features of the physical environment (e.g., space, appeal, comfort and convenience) can significantly affect patientsÕ outcome and facilitate adaptive behaviors (Earls & Nelson, 1988;Gutkowski, Ginath, & Guttmann, 1992;Timko, 1996;Younge, Oetting, Banning, & Younge, 1990-1991Whitehead, Polsky, Crookshank, & Fik, 1984).…”
Section: Introductionmentioning
confidence: 92%
“…Other studies have confirmed that greater community acceptance and lower levels of rejection are associated with increased integration (Nelson, Hall, Squire, & Walsch-Bowers, 1992;Segal & Aviram, 1978;Sherman, Frenkel, & Newman, 1986). City population density has been yet another community factor identified as a predictor of integration (Kruzich, 1985).…”
Section: Determinants Of Community Integrationmentioning
confidence: 94%
“…The close proximity to community resources is a salutary feature of SIL programs because prior studies in other mental health residential settings have noted a significant role that resource accessibility plays in enabling residents' integration (Kruzich, 1985;Segal & Aviram, 1978;Segal & Everett-Dille, 1980;Timko, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, the Assertive Community Treatment (ACT) model, an evidence-based intervention originated as an alternative to psychiatric hospitalization (Stein & Test, 1980;1985), has been used in service provisions for the homeless mentally ill population with demonstrated effectiveness in increasing residential stability, reducing homelessness, and reducing hospitalization (Lehman, Dixon, Kernan, DeForge, & Postrado, 1997;Tsemberis, 1999;Tsemberis, Gulcur, & Nakae, 2004).…”
Section: Background Of Supported Housingmentioning
confidence: 99%